Parameters influence of windshield curvature on pedestrian head injuries based on reverse engineering. Issue 2 (June 2019) - Zhao, H G; Shi, H J; Li, C S; Yang, N
Abstract: With the development of the automobile industry, the problems of traffic accidents have attracted more and more attention, and many countries are also attaching importance to pedestrian protection. In the collision process of vehicle and pedestrian, the head of pedestrian is very easy to collide with the engine cover and windshield of the car, which causes fatal damage. In this paper, the curvature of four kinds of automobile front windshields is studied by reverse engineering and simulation experiments. By using reverse engineering software to dispose the scanned point cloud data, a smooth surface is derived, and finite element software is used to establish the model of the pedestrian head impactor hitting the windscreen of the car, and finally the simulation processing is carried out. Simulation results show that Head Injury Criteria is positively correlated with the transverse curvature of the front windshield and negatively correlated with the longitudinal curvature.